2000
DOI: 10.4315/0362-028x-63.11.1503
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Spore Inhibition and Inactivation in Foods by Pressure, Chemical Preservatives, and Mild Heat

Abstract: Sucrose laurates, sucrose palmitate, sucrose stearates, and monolaurin (Lauricidin) were evaluated for inhibitory effects against spores of Bacillus sp., Clostridium sporogenes PA3679, and Alicyclobacillus sp. in a model agar system. The combined treatment of sucrose laurate, high hydrostatic pressure, and mild heat was evaluated on spores of Bacillus and Alicyclobacillus in foods. The minimum inhibitory concentrations of the sucrose esters were higher than that of Lauricidin for all spores tested in the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 20 publications
3
43
0
2
Order By: Relevance
“…Smith et al (11) synthesized various carbohydrate esters and found that the carbohydrate moiety can markedly influence the microbial inhibitory activity of the fatty acid. The activity of sugar esters has been suggested to be antimicrobial (2), while others have suggested they have just bacteriostatic activity (10). All published studies investigating the activity of sugar esters only provide the MICs; there are no publications that determined the minimal bactericidal concentrations (MBCs) of sugar esters.…”
mentioning
confidence: 99%
“…Smith et al (11) synthesized various carbohydrate esters and found that the carbohydrate moiety can markedly influence the microbial inhibitory activity of the fatty acid. The activity of sugar esters has been suggested to be antimicrobial (2), while others have suggested they have just bacteriostatic activity (10). All published studies investigating the activity of sugar esters only provide the MICs; there are no publications that determined the minimal bactericidal concentrations (MBCs) of sugar esters.…”
mentioning
confidence: 99%
“…For example, Chaibi et al (1998) reported a significant reduction in the heat resistance of Bacillus cereus spores treated at 91e97 C (0.1 MPa) in phosphate buffer in the presence of 0.005 mol L À1 monolaurin. Shearer et al (2000) also reported a 3.0-log reduction of Bacillus subtilis spores in milk treated at 392 MPa and 45 C for 10 min in the presence of monolaurin added at a concentration as low as 0.001%. No significant spore inactivation (P > 0.05) was achieved by a 2-min PATP treatment in the absence of antimicrobial compounds at pH 7.0 (only a 0.4 log reduction) (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…and C. sporogenes spores in a model agar system (monolaurin); enhanced high-pressure inactivation of B. subtilis spores in milk (monolaurin) Chaibi, Ababouch, and Busta (1996); Chaibi et al (1998); Shearer et al (2000) Preservative salts Sodium benzoate (0.5 g L À1 ) and sodium nitrite (2 g L À1 )…”
Section: Monoglyceridesmentioning
confidence: 99%
See 1 more Smart Citation
“…nisin and sucrose laurate), or an additional control hurdle (e.g. olive powder) to inactivate B. cereus spores has been investigated (Aoyama et al, 2005;Arroyo et al, 1997;Evelyn and Silva, 2015b;Fornari et al, 1995;Gola et al, 1996;Ju et al, 2008;Lopez-Pedemonte et al, 2003;Luu-Thi et al, 2014;Marco et al, 2011;McClements et al, 2001;Meyer, 2000;Raso et al, 1998;Robertson et al, 2008;Rovere et al, 1998;Scurrah et al, 2006;Shearer et al, 2000;Shigeta et al, 2007;van Opstal et al, 2004). B. cereus spore log reductions between 1 and ≥ 7 were achieved, depending on the conditions applied and the spore resistance.…”
Section: Introductionmentioning
confidence: 98%